Chronology and Eruption Dynamics of the Historic∼1700 CE Eruption of Tseax Volcano, British Columbia, Canada - Le Moigne, Yannick; Williams-Jones, Glyn; Vigouroux, Nathalie; Russell, James K. (Frontiers in Earth Science, 2022)
Despite having relatively short timespans of eruptions, monogenetic volcanoes can pose significant risks to the nearby population. Here, we describe the ∼1700 CE eruption of Tseax volcano, British Columbia, which killed up to 2,000 people of the Nisga’a First Nation and is ranked as Canada’s worst natural disaster. Within the Nisga’a culture, Adaawak stories preserve an observational account of the Tseax eruption. In this study, we establish the chronology of the eruption by integrating field observations and petrophysical data informed by Nisga’a oral and written histories. The Nisga’a stories corroborate the short duration and exceptional intensity of the eruption as recorded in the volcanic products. The eruption was divided in two main periods: 1) Period A and 2) Period B. 1) The eruption started in a typical Hawaiian style with low levels of lava fountaining that built up a spatter rampart. This pyroclastic edifice was breached by voluminous pāhoehoe lavas erupted at high discharge rates. We estimate that almost half of the emplaced lava volume (0.20 km3) was erupted in Period A and had a flux of 800–1,000 m3/s. The low viscosity lava reached the Nass Valley, 20 km downstream of the volcano, in “swift currents”, and engulfed the former Nisga’a villages in only 1–3 days, thus likely being responsible for the reported fatalities. The discharge rates progressively diminished to 10–200 m3/s until the end of this first eruptive period, which lasted a few weeks to a few hundred days. 2) The Period B eruption produced two ‘a‘ā lavas with discharge rates <50 m3/s. This period was also characterised by an explosive phase of eruption that built a 70 m high tephra cone overlapping with a spatter rampart; Period B lasted approximately 20 days. In total, the eruption produced 0.5 km3 of volcanic materials (mostly in the form of lava flows) on the order of weeks to a few months. The mountainous terrain significantly controlled the emplacement of lava flows that reached long distances in a short amount of time. Our work shows that, under certain conditions, eruptions of small-volume monogenetic volcanoes ca pose risks comparable to flank eruptions on long-lived shield volcanoes.